INTEGRASI ILMU EKONOMI ISLAM DAN PENDIDIKAN AGAMA ISLAM ERA SOCIETY 5.0 - Muzakki, Zubairi (Islamic Banking & Economic Law Studies (I-BEST), 2023)
In the era of Society 5.0 which is marked by the rapid development of digital technology and a shift in the paradigm of society, the integration between economics and Islamic religious education is becoming increasingly relevant and important. This integration provides a strong foundation in facing economic and spiritual challenges amidst rapid social change. Economics is a scientific discipline that studies how people allocate limited resources to meet their needs and wants. On the other hand, Islamic religious education emphasizes character building and basic spiritual values​​for individual Muslims. The combination of these two fields can provide a comprehensive understanding of how to manage resources fairly and sustainably, while still considering spiritual and moral aspects in making economic decisions. The integration of economics and Islamic religious education in the Society 5.0 era can be carried out through an interdisciplinary approach in teaching and research. Islamic religious education can provide an ethical and moral foundation for economic decision-making, while economics provides an analytical framework and instruments for analyzing complex economic phenomena.In addition, this integration can generate innovative thinking in facing global economic challenges. The principles of a just and sustainable economy taught in economics can be applied in the context of Islamic religious values, such as social justice, income distribution and environmental sustainability.By integrating economics and Islamic religious education, we can produce graduates who not only have a strong understanding of economic concepts, but also have moral integrity and spiritual awareness. They will be able to respondto economic challenges by prioritizing the principles of justice, ethics and sustainability, in line with Islamic religious values.In conclusion, the integration of economics and Islamic religious education in the era of Society 5.0 brings great benefits in dealing with the complexity of economic and spiritual challenges. Through an interdisciplinary approach, we can develop a holistic understanding of a just and sustainable economy, which is in harmony with Islamic religious principles. Thus, this integration can become the basis for building a more harmonious and sustainable society in the era of Society 5.0